2021
DOI: 10.25078/yb.v4i1.2214
|View full text |Cite
|
Sign up to set email alerts
|

Learn from Home with a Simple Think Pair Share

Abstract: When learn from home becomes a new normal, teachers should switch the class to online. Meanwhile, mastering writing skill is still important in online class because the subjects will be able to express their ideas, feeling and experiences in the written form appropriately. The objective of this study was to find out whether or not writing skill of second semester students of English Language Education Study Program, Faculty of Teacher Training, Mahasaraswati Denpasar University in Academic year 2019/2020 could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Students also develop Mathematical problem-solving skills, apply knowledge to solve mathematical problems in everyday life, interaction with classmates, exchange knowledge, acceptance of others' opinions, have confidence, assertiveness in group discussions and a positive attitude towards Mathematics. Reference [14] said Think-Pair-Share can make students more creative in writing, gives the students a chance to discuss their individual solutions with other students and increases their confidence before presenting their idea to the classroom and reference [13] show he was found that the students who learned by using collaborative learning and think-pair-share technique for interest and the value of money revealed higher Mathematical problem-solving skills 4 items, 8 points each, totaling 32 points. Those who learned using the conventional approach at the .01 level of significance.…”
Section: Research Instrumentmentioning
confidence: 99%
“…Students also develop Mathematical problem-solving skills, apply knowledge to solve mathematical problems in everyday life, interaction with classmates, exchange knowledge, acceptance of others' opinions, have confidence, assertiveness in group discussions and a positive attitude towards Mathematics. Reference [14] said Think-Pair-Share can make students more creative in writing, gives the students a chance to discuss their individual solutions with other students and increases their confidence before presenting their idea to the classroom and reference [13] show he was found that the students who learned by using collaborative learning and think-pair-share technique for interest and the value of money revealed higher Mathematical problem-solving skills 4 items, 8 points each, totaling 32 points. Those who learned using the conventional approach at the .01 level of significance.…”
Section: Research Instrumentmentioning
confidence: 99%